Safety and efficacy of apixaban versus vitamin K antagonists in patients undergoing dialysis: a systematic review and meta-analysis - Yifang Zhang; Jialiang Wang; Nannan Shen; Jie Jiang; Yanna Xie (Renal Failure)
Background This review aims to evaluate the safety and efficacy of apixaban vs. vitamin K antagonists (VKAs) in patients on dialysis.Methods All types of studies published on PubMed, Embase, CENTRAL, and Web of Science up to 10 September 2023 and comparing outcomes of apixaban vs. VKA in dialysis patients were eligible.Results Two randomized controlled trials (RCTs) and six retrospective studies were included. Apixaban treatment was associated with significantly lower risk of major bleeding (RR: 0.61; 95% CI: 0.48, 0.77; I2 = 50%) and clinically relevant non-major bleeding (RR: 0.82, 95% CI: 0.68, 0.98, I2 = 9%) compared to VKA. Meta-analysis also showed that the risk of gastrointestinal bleeding (RR: 0.74, 95% CI: 0.64, 0.85, I2 = 16%) and intracranial bleeding (RR: 0.64, 95% CI: 0.49, 0.84, I2 = 0%) was significantly reduced with apixaban. Meta-analysis showed no difference in the risk of ischemic stroke (RR: 0.40, 95% CI: 0.06, 2.69, I2 = 0%), mortality (RR: 1.26, 95% CI: 0.74, 2.16, I2 = 94%) and recurrent venous thromboembolism (RR: 1.02, 95% CI: 0.87, 1.21, I2 = 0%) between the two groups. Subgroup analysis of RCTs showed no difference in bleeding outcomes.Conclusions Low-quality evidence from a mix of RCTs and retrospective studies shows that apixaban may have better safety and equivalent efficacy as compared to VKA in dialysis patients. Apixaban treatment correlated with significantly reduced risk of major bleeding and clinically relevant nonmajor bleeding in observational studies but not in RCTs. The predominance of retrospective data warrants caution in the interpretation of results.